2023
DOI: 10.1186/s41155-023-00276-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short video app-guided loving-kindness meditation on college students’ mindfulness, self-compassion, positive psychological capital, and suicide ideation

Chao Liu,
Hao Chen,
Ayuan Zhang
et al.

Abstract: Objective The study investigated the effects of a short video app guided loving-kindness meditation (LKM) on college students’ mindfulness, self-compassion, positive psychological capital, and suicide ideation. The purpose of the study is to investigate the intervention effect of LKM training on suicidal ideation among college students with the help of the short video application and to provide an empirical basis for the exploration of early suicide intervention strategies for college students.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
2
0
2
Order By: Relevance
“…Previous research indicates that online guided compassion meditations are as effective as their offline counterparts. This finding underscores the potential of digital platforms to deliver psychological benefits comparable to traditional methods (Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 54%
“…Previous research indicates that online guided compassion meditations are as effective as their offline counterparts. This finding underscores the potential of digital platforms to deliver psychological benefits comparable to traditional methods (Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 54%
“…Tema Objetivo Participantes (Liu et al, 2023) Los efectos de la meditación de bondad amorosa guiada por una aplicación de vídeo breve sobre la atención plena, la autocompasión, el capital psicológico positivo y la ideación suicida de los estudiantes universitarios…”
Section: Fuenteunclassified
“…Tema Metodología Resultados (Liu et al, 2023) Los efectos de la meditación de bondad amorosa guiada por una aplicación de vídeo breve sobre la atención plena, la autocompasión, el capital psicológico positivo y la ideación suicida de los estudiantes universitarios Los participantes se dividieron en dos grupos: uso de aplicaciones (n = 37) y control (n = 37). El grupo de la aplicación recibió la intervención durante 8 semanas, Se evaluó: atención plena, autocompasión, capital psicológico positivo e ideación suicida antes y después de la intervención en el uso de la aplicación.…”
Section: Fuenteunclassified
“…Over the past decade, mindfulness-based interventions have grown in acceptance among colleges worldwide. Short-term mindfulness-based stress reduction programs have been implemented in various formats, such as video apps, online interactions, meditations, and group settings (Chesin and Jeglic 2022;Liu et al 2023;MacDonald and Neville 2023). A literature review of 57 studies on the effectiveness of mindfulness with college students has shown that MBSR decreased stress in 73% of studies, while reducing anxiety in 100% (Bamber and Schneider 2015).…”
Section: Literature Reviewmentioning
confidence: 99%